2021
DOI: 10.1111/liv.14915
|View full text |Cite
|
Sign up to set email alerts
|

Deaths from hepatocellular carcinoma are more likely to occur in medical facilities than deaths from other cancers: 2003‐2018

Abstract: Place of death is a key indicator of quality of end‐of‐life care, and most people with a terminal diagnosis prefer to die at home. Home has surpassed the hospital as the most common location of all‐cause and total cancer‐related deaths in the United States. However, trends in place of death due to hepatocellular carcinoma (HCC), which is uniquely comanaged by hepatologists and oncologists, have not been described. We analysed US death certificate data from 2003 to 2018 for the proportion of deaths over time at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A report from Germany found that HCC in males is four-times more common than HCC in females [ 4 ]. Patients with HCC tend to have end of life care in hospitals with a proportion of 15.2% of patients with the short survival time of 1.8 months in advanced stage if left untreated [ 5 , 6 ].…”
mentioning
confidence: 99%
“…A report from Germany found that HCC in males is four-times more common than HCC in females [ 4 ]. Patients with HCC tend to have end of life care in hospitals with a proportion of 15.2% of patients with the short survival time of 1.8 months in advanced stage if left untreated [ 5 , 6 ].…”
mentioning
confidence: 99%